Design and analysis of improved second order generalized integrator‐based voltage and frequency controller for permanent magnet synchronous generator operating in small‐hydro system feeding single‐phase loads. (14th February 2019) - Chandran, Vineet P.; Murshid, Shadab; Singh, Bhim
Summary: The voltage and frequency controller (VFC) for a small hydro generator system is implemented for maintaining constant voltage and frequency across the terminals of a permanent magnet synchronous generator (PMSG) feeding single‐phase consumer loads in remote areas. The system comprises of a voltage source converter (VSC), which DC‐link is integrated to an insulated gate bipolar transistor switch‐based DC‐DC converter to form a VFC. Along with the terminal voltage, the system also maintains constant frequency by feeding extra power into the auxiliary load, which is controlled by an insulated‐gate bipolar transistor (IGBT) switch. An improved second order generalized integrator (ISOGI)‐based control algorithm is used to generate switching pulses for VSC. In this algorithm, a third integrator is added to eliminate DC offset. A damping factor of small value is introduced in this algorithm to damp out oscillations quickly during dynamic load changes. VSC is connected to the point of common coupling (PCC) to supply the required amount of reactive power during its operation and to maintain the DC‐link voltage. Moreover, the VSC is also responsible for power quality improvement by load balancing, harmonics suppression, and maintaining total harmonic distortion (THD) of voltage and current within the prescribed limits. A prototype feeding single‐phase consumer loads are developed in the laboratory using ISOGI‐based control algorithm, and test results for different loading condition are demonstrated for effectiveness of the control algorithm.